Social networks and cognitive function in older adults: findings from the HAPIEE study - Nie, Yifan; Richards, Marcus; Kubinova, Ruzena; Titarenko, Anastasiya; Malyutina, Sofia; Kozela, Magdalena; Pajak, Andrzej; Bobak, Martin; Ruiz, Milagros (BMC geriatrics, 2021)
BACKGROUND: Social networks are associated with better cognitive health in older people, but the role of specific aspects of the social network remains unclear. This is especially the case in Central and Eastern Europe. This study examined associations between three aspects of the social network (network size of friends and relatives, contact frequency with friends and relatives, and social activity participation) with cognitive functions (verbal memory, learning ability, verbal fluency, processing speed, and global cognitive function) in older Czech, Polish, and Russian adults. METHODS: Linear regression estimated associations between baseline social networks and cognitive domains measured at both baseline and follow-up (mean duration of follow-up, 3.5 ± 0.7 years) in 6691 participants (mean age, 62.2 ± 6.0 years; 53.7% women) from the Health, Alcohol and Psychosocial factors In Eastern Europe (HAPIEE) study. RESULTS: Cross-sectional analyses, adjusted for country, age, and sex, showed positive associations of global cognitive function with social activity participation and network size of friends and relatives, but not with contact frequency in either network. Further adjustment for sociodemographic, behavioural, and health characteristics attenuated the associations with network size of relatives (P-trend = 0.074) but not with network size of friends (P-trend = 0.036) or social activities (P-trend< 0.001). In prospective analyses, network size and social activity participation were also linked with better cognition in simple models, but the associations were much stronger for social activities (P-trend< 0.001) than for network size of friends (P-trend = 0.095) and relatives (P-trend = 0.425). Adjustment for baseline cognition largely explained the prospective associations with network size of friends (P-trend = 0.787) and relatives (P-trend = 0.815), but it only slightly attenuated the association with social activities (P-trend< 0.001). The prospective effect of social activities was largely explained by sociodemographic, health behavioural, and health covariates (P-trend = 0.233). Analyses of specific cognitive domains generally replicated the cross-sectional and prospective findings for global cognitive function. CONCLUSIONS: Older Central and Eastern European adults with larger social networks and greater social activities participation had better cognitive function, but these associations were stronger at baseline than over the short-term follow-up.
Keywords: Russia; Friends; Cross-Sectional Studies; Male; Poland; Aged; mužské pohlaví; senioři; sociální sítě; přátelé; Ageing; Czech Republic; kognice; lidé; ženské pohlaví; Humans; Social Networking; Social networks; Cognitive function; průřezové studie; Cognitive decline; Female; Polsko; Social relationships; Cognition